Exercise motives in a sample of Brazilian university students - Guedes,Dartagnan Pinto (2013)
The present study aimed to identify the exercise motives according to selected socio-demographic indicators in university students. The sample was comprised of 2,380 individuals (1,213 men and 1,167 women) aged between 18 and 35 years. The exercise motives were identified with the Portuguese-translated version of the Exercise Motivations Inventory (EMI-2). University students gave significantly greater importance to exercise for reasons identified as Disease Prevention. Factors that are less relevant in statistical language were identified in a context of motivation associated with Social Recognition and Competition. Sex, age, family economic class, experience with exercise and body weight had a significant effect on the level of importance of exercise among university students. In conclusion, the results found can contribute to the development of physical activity promotion programs and a possible reduction in the number of dropouts among university students.